The severity of inflammation in major neuropsychiatric disorders: comparison of neutrophil-lymphocyte and platelet-lymphocyte ratios between schizophrenia, bipolar mania, bipolar depression, major depressive disorder, and obsessive compulsive disorder - YORGUNER, NEŞE (TAYLOR & FRANCIS LTD, 2021)
Background As non-specific markers of immune dysregulation, neutrophil-lymphocyte and platelet-lymphocyte ratios (NLR and PLR) have been consistently shown to be increased in major neuropsychiatric disorders. Although this increase seems to be trans-diagnostic, the extent to which its magnitude differs between disorders remains largely unclear. Aim The aim of this study was to directly compare the severity of inflammation (as reflected by NLR and PLR) between schizophrenia (Sch), bipolar mania (BD-M), bipolar depression (BD-D), major depressive disorder (MDD) and obsessive compulsive disorder (OCD). Methods NLR and PLR were obtained for a total of 417 subjects (91 Sch, 70 BD-D, 37 BD-M, 93 MDD, 37 OCD, and 95 controls) and analyzed for group differences. Results Sch, BD-M, BD-D and MDD presented with significantly higher NLR compared with both OCD and HC. NLR in BD-M was significantly higher than all the remaining groups, whereas Sch, BD-D and MDD presented with comparably elevated NLR. Moreover, BD-M, Sch and MDD had significantly higher PLR compared with HC. Conclusion These results suggest that the underlying inflammation may be most severe in BD-M, followed by Sch, BD-D and MDD. On the other hand, inflammation may be of negligible intensity in OCD, or at least undetectable by means of NLR or PLR.
Keywords: Inflammation; schizophrenia; bipolar disorder; major depressive disorder; obsessive compulsive disorder; C-REACTIVE PROTEIN; NEUTROPHIL/LYMPHOCYTE RATIO; PSYCHOTIC FEATURES; OXIDATIVE STRESS; DISEASE-ACTIVITY; SYMPTOMS; MARKERS; MOOD; METAANALYSIS; ASSOCIATION